GASTOS TRIBUTÁRIOS EM TRAJETÓRIA: ANÁLISE DAS POLÍTICAS DE RENÚNCIA FISCAL DA UNIÃO ENTRE 1996-2019 - Oliveira, Joao Lucas Mattos Bodart de (2020)
To date, many of the debates related to public policies have been directed at the scope of the tax structure of the Brazilian State and the importance of reforming its dysfunctional fra-mework. One aspect that stands out in this is its high level of regre